Presentation and outcomes of Kawasaki disease in Latin American infants younger than 6 months of age: a multinational multicenter study of the REKAMLATINA network (2020)
Objective: To characterize the clinical presentation and outcomes of Kawasaki disease (KD) in infants <6 months of age as compared to those ≥6 months in Latin America. Methods: We evaluated 36 infants <6 months old and 940 infants ≥6 months old diagnosed with KD in Latin America. We compared differences in laboratory data, clinical presentation, treatment response, and coronary artery outcomes between the two cohorts. Results: The majority (78.1%) of infants and children ≥6 months of age were initially diagnosed with KD, as compared to only 38.2% of infants <6 months. Clinical features of KD were more commonly observed in the older cohort: oral changes (92 vs. 75%, P = 0.0023), extremity changes (74.6 vs. 57.1%, P = 0.029), and cervical lymphadenopathy (67.6 vs. 37.1%, P = 0.0004). Whether treated in the first 10 days of illness or after the 10th day, infants <6 months were at greater risk of developing a coronary artery aneurysm compared to KD patients ≥6 months treated at the same point in the course of illness [ ≤ 10 days (53.8 vs. 9.4%, P = 0.00012); >10 days (50 vs. 7.4%, P = 0.043)]. Conclusion: Our data show that despite treatment in the first 10 days of illness, infants <6 months of age in Latin America have a higher risk of developing a coronary artery aneurysm. Delay in the diagnosis leads to larger coronary artery aneurysms disproportionately in these infants. Thus, suspicion for KD should be high in this vulnerable population.